2015
DOI: 10.1063/1.4915618
|View full text |Cite
|
Sign up to set email alerts
|

Photon antibunching in single-walled carbon nanotubes at telecommunication wavelengths and room temperature

Abstract: We investigated the photoluminescence of individual air-suspended single-walled carbon nanotubes (SWNTs) from 6 to 300 K. Time-resolved and antibunching measurements over the telecommunication wavelength range were performed using a superconducting single-photon detector. We detected moderate temperature independent antibunching behavior over the whole temperature range studied. To investigate the exciton dynamics, which is responsible for the antibunching behavior, we measured excitation-power and temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 32 publications
3
33
0
Order By: Relevance
“…As NIR photoluminescent materials, SWNTs are expected to be of practical use in the imaging of biological tissues, telecommunications, and other applications. [4][5][6][7][8] Recently, it has been reported that the chemical functionalization of SWNTs, such as photooxidation, arylation, and alkylation, induces bright and red-shied NIR PL peaks. [9][10][11][12][13][14][15][16][17][18][19] Based on density functional theory (DFT) calculations, it was proposed that the new PL peak is derived from splitting of the frontier orbitals of SWNTs by sidewall functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…As NIR photoluminescent materials, SWNTs are expected to be of practical use in the imaging of biological tissues, telecommunications, and other applications. [4][5][6][7][8] Recently, it has been reported that the chemical functionalization of SWNTs, such as photooxidation, arylation, and alkylation, induces bright and red-shied NIR PL peaks. [9][10][11][12][13][14][15][16][17][18][19] Based on density functional theory (DFT) calculations, it was proposed that the new PL peak is derived from splitting of the frontier orbitals of SWNTs by sidewall functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the absorption and photoluminescence (PL) of the SWNTs arise in the near infra-red (NIR) region by the Van Hove singularity 2 . Based on the advantage of the NIR PL in the high transparency for biological tissues and in the telecommunication wavelengths, applications for imaging, sensing and optical devices have been widely studied 3 4 5 6 7 8 . A fundamental drawback of the SWNT materials, however, is the low quantum yield (φ < 1%) 9 due to i) optically-forbidden transition states for dark exciton that exist at the lower energy levels than the optically-allowed transition states for the bright exciton 10 , and ii) exciton quenching through collision with defect sites 11 or with other excitons 12 that can frequently occur owing to the 1D-confined structure.…”
mentioning
confidence: 99%
“…
Single-Wall Carbon Nanotubes (SWNTs) are among the very few candidates for single-photon sources operating in the telecom bands since they exhibit large photon antibunching up to room temperature [1][2][3][4][5]. However, coupling a nanotube to a photonic structure is highly challenging because of the random location and emission wavelength in the growth process [6][7][8][9].
…”
mentioning
confidence: 99%